Life stories: Unraveling the academic configuration of a multifaceted and multidisciplinary field of knowledge - López-Montero, Rocío; García-Navarro, Carmen; Delgado-Baena, Antonio; Vela-Jiménez, Rocío; Sianes, Antonio (Frontiers in Psychology, 2022)
In the field of qualitative research, life stories are consolidated as one of the most important techniques within the biographical method. However, due to the multiplicity of techniques covered by this method and the disciplines in which it is applied, the contributions and scope of life histories do not present a clear delimitation. By contrast, a considerable conceptual confusion persists and the transfer of its production remains very narrow. In this sense, this article aims to clarify the field of knowledge generated through life stories. To this end, it innovatively applies the bibliometric method. Making use of performance analysis and scientific mapping through the VosViewer application, it studies a body of 2670 articles indexed in the Web of Science. The results show how knowledge transferred from psychology through its major schools of thought occupies a central place. This leaves in a secondary position the knowledge produced by other disciplines such as sociology or anthropology, which is not transferred in the main forums of scientific impact. In this way, the conclusion points to the need to open up new lines of research to find out the differences between the different techniques and disciplines when applying this methodology.